Techniques for seedling production of two native grasses: new perspectives for Brazilian Cerrado restoration - Oliveira, Ana C. C.; Forti, Victor A.; Paula Loiola, Priscilla; Viani, Ricardo A. G. (Restoration ecology, 2020)
There is a major need for restoration of nonforest ecosystems in the Brazilian Cerrado, and planting seedlings is promising. However, there is no currently available information on nontree species production in nurseries. Grasses are dominant in the Cerrado herbaceous layer; therefore, we tested whether tree seedling production techniques can be used for two native grasses widely spread across the Cerrado ecoregion (Schizachyrium sanguineum and Loudetiopsis chrysothrix). We performed a factorial experiment with three levels: (1) seedbed substrate, (2) container volume, and (3) final substrate. Seeds were germinated in seedbeds with native soil or sand and, after emergence, transferred to 30, 55, or 290 cm3 containers filled with native soil, commercial substrate, or a mixture thereof. We evaluated seedling survival, height relative growth rate (RGR), tillering, and dry biomass. Survival rates after transfer from seedbeds to containers were greater than 80% for both species. Generally, species had greater height RGR, tillering, and biomass in the 290 cm3 containers than in the other containers, and the presence of native soil in the seedbeds, as well as in the containers, fostered seedling growth. However, the use of native soil is not recommended for large‐scale production, because its acquisition could degrade Cerrado areas. The commercial substrate improvement could be an alternative to increase seedling growth, since grasses survived well and presented greater growth in the largest container. Our study demonstrated that the techniques currently used in commercial nurseries for growing trees are suitable for both grasses, and substrates and container size drive seedling growth.